The ridiculous philosopher: Socrates as a dramatization of the Platonic thesis on the comical - Ramos Gall, Felipe (Revista Archai, 2024)
The purpose of this paper is to show the dramatic importance of the Platonic thesis on the comical within the very economy of the dialogues. The guiding hypothesis will be that the conception that Plato develops about the comical or ridiculous, especially in the Philebus, mixes with the characterization of Socrates and with his way of philosophizing. Therefore, what we intend to demonstrate is that the figure of Socrates, who, as a character of Plato, is the incarnation of the paradigm of philosophical life par excellence, manifests by his own dramatization in the dialogues the very nature of the comical according to the Platonic conceptualization.